(untitled) (Journal of Economic Research & Business Administration, 2019)
The formation of a highly efficient, competitive tourism industry integrated into the global tourism market system requires the development of domestic and inbound tourism, regional cultural and tourist clusters; increasing the share of the tourist industry in the country’s economy and the quality of the tourist product, attracting investment and promoting tourist destinations in the domestic and international markets. Therefore, the relevance of the topic determines that the problems raised by the authors in the article require a comprehensive study and analysis, the preparation of scientific substantiation. The strategic vision of the development of the tourism industry in the Republic of Kazakhstan is the statement of Kazakhstan as a globally recognizable tourist destination. The main purpose of the article is to solve problems and determine the prospects for the development of the tourism industry in the city of Astana and the Akmola region, to identify barriers and constraints taking into account the current situation in the economy. Based on the identified goal, the authors analyzed the main indicators of the tourism industry, its strengths and weaknesses in accordance with the tourism competitiveness index, identified factors affecting problem solving, studied the institutional infrastructure of state support for the development of the tourism industry in Astana and Akmola region, development tools of the tourism industry of the Republic of Kazakhstan and gave specific proposals aimed at solving the problems impeding the development of tourism.